Analysis of Biomass Energy Potential in North Sumatra Using LEAP - Fadli, Rizki; Mawardi, Mawardi; Novalianda, Sari; Irawan, Ade; Rizky, Muhammad; Irawan, Lutfi; Rida, Rizkha (Universitas Harapan Medan, 2024)
This research aims to evaluate the biomass energy potential in North Sumatra using the Long-range Energy Alternatives Planning (LEAP) system. North Sumatra, a region rich in agricultural and forestry resources, presents significant opportunities for biomass energy development. The LEAP model, a widely used tool for energy policy analysis and climate change mitigation assessment, was employed to simulate and analyze various scenarios of biomass energy utilization in the region. Key biomass resources in North Sumatra, such as palm oil residues, rice husks, and wood waste, were identified and quantified. The study involved the collection of data on biomass availability, current usage patterns, and technological options for biomass energy conversion. By integrating these data into the LEAP model, different scenarios were developed to explore the potential contributions of biomass energy to the regional energy mix and greenhouse gas (GHG) emissions reduction. The analysis results show that in 2028, the significant potential for new and renewable energy in North Sumatra includes water energy, wind energy and biomass energy. The potential biomass energy produced is 27.0 MW.